MODERN PROBLEMS OF CARRYING OUT POLICY OF IMPORT SUBSTITUTION IN PHARMACEUTICAL INDUSTRY IN RUSSIA - O. Mishina; Z. Korzovatykh (Вестник университета)
When carrying out policy of import substitution in pharmaceutical industry first of all it is necessary to pay attention to the problems existing in this industry today. On the basis of the analysis of industry of pharmaceutics in Russia, the authors have revealed the main problems of industry, and also the possible directions of carrying out policy of import substitution are created.